The relationship between social responsibility and marital conflicts in couples with the mediating role of optimistic and self-regulatory - Reyhaneh Hashempour Mafsali; Mahmoud Jajarmi; Hamzeh Akbari (Shahid Beheshti University of Medical Sciences, 2022)
Background: Marital conflicts are a precursor to the separation of couples and can range from obvious differences in the views of man and woman to serious differences in goals, values ​​and aspirations. The aim of this study was to investigate the relationship between social responsibility and marital conflicts in couples with the mediating role of optimism and self- regulatory. Methods: The present study was a descriptive-survey and correlational study. The statistical population included couples who referred to Bahar Andisheh Clinic in Mashhad in 2020-2021 and 300 people were selected by convenience sampling. Responsibility, marital conflicts, self-regulation and optimism questionnaires were used to collect data. Data were analyzed using SPSS 23 software and Pearson correlation test (structural equation). Results: The results revealed that 68% of the variance related to marital conflicts was explained by the social responsibility, optimism, and self-regulation. Responsibility showed a direct and significant relationship with optimism and self-regulation (r= 0.597 and 0.736, respectively and P < 0.001), and had a negative and significant relationship with marital conflicts (P-value < 0.001). Conclusion: Based on the results, the sense of social responsibility reduces marital conflicts and with increasing optimism and self-regulation, couple's conflicts decrease. It is suggested that educational interventions be held to strengthen and improve the level of responsibility, optimism and self-regulation in order to reduce marital conflicts.